Respuesta :
Answer:
In my opinion the answer is y = 6
Step-by-step explanation:
We have two unknowns from the equation therefore, two equations are needed. These equations are:
3x + y = 9
y = –4x +10
To solve for y, we first substitute the second equation to the first one.
3x + –4x +10= 9
x = 1
We substitute the value of x to either of the equations and solve for y.
y = –4(1) +10
y = 6
Answer:
y=6
Step-by-step explanation:
[tex]3x + y = 9[/tex]
[tex]y = -4x + 10[/tex]
Substitute the value of y in the first equation:
[tex]3x + (-4x + 10) = 9[/tex]
Apply the subtraction property of equality:
[tex]-x + 10 = 9[/tex]
[tex]-x=-1[/tex]
x=1
Substitute 1 for x in the given y equation
[tex]y = -4x + 10[/tex]
[tex]y = -4(1)+ 10[/tex]
y=6